Two-dimensional semiconductors based field-effect transistors: review of major milestones and challenges - Nandan, Keshari; Agarwal, Amit; Bhowmick, Somnath; Chauhan, Yogesh S. (Frontiers in Electronics, 2023)
Two-dimensional (2-D) semiconductors are emerging as strong contenders for the future of Angstrom technology nodes. Their potential lies in enhanced device scaling and energyefficient switching compared to traditional bulk semiconductors like Si, Ge, and III-V compounds.These materials offer significant advantages, particularly in ultra-thin devices with atomic scale thicknesses. Their unique structures enable the creation of one-dimensional nanoribbons and vertical and lateral heterostructures. This versatility in design, coupled with their distinctive properties, paves the way for efficient energy switching in electronic devices. Moreover, 2-D semiconductors offer opportunities for integrating metallic nanoribbons, carbon nanotubes (CNT), and graphene with their 2-D channel materials. This integration helps overcome lithography limitations for gate patterning, allowing the realization of ultra-short gate dimensions. Considering these factors, the potential of 2-D semiconductors in electronics is vast. This concise review focuses on the latest advancements and engineering strategies in 2-D logic devices.